Occurrence of Leptospira sp. In environmental water samples from wind cave, Bau, Sarawak - Irwin Emmanuel, ak Robin Jeli (Universiti Malaysia Sarawak, UNIMAS, 2013)
The genus Leptospira is composed of tightly coiled spirochetes that exist in two groups which are pathogenic strains and saprophytic strains. The pathogenic strains caused Leptospirosis, the most widespread zoonotic disease which is also known as the rat urine’s disease. The saprophytic strains are usually found on surface water meanwhile the pathogenic strains requires animal host to survive. The aim of this research is determine the occurrence of Leptospira sp. isolated from environmental water samples collected from Wind Cave, Bau. A total of 17 water samples were collected from the sampling site. The samples were cultured in EMJH medium for 30 days and were observed under dark field microscope for the presence of Leptospira. No observation of leptospires was detected. Six samples were selected for comparison purposes. Further confirmation was done by utilizing polymerase chain reaction targeting the LipL32 gene. The findings reported that LipL32 gene was successfully amplified by PCR in three of the samples. Therefore, the use of PCR by targeting the LipL32 gene is more reliable compared to direct observation under dark field microscope in detecting Leptopsira in environmental water.